OXIDATIVE DEHYDROGENATION OF 1-TETRALONES: SYNTHESIS OF JUGLONE, NAPHTHAZARIN, AND ?-HYDROXYANTHRAQUINONES (Journal of Sciences, Islamic Republic of Iran)
Treatment of 5,8-dihydroxy-1-tetralone (9) with either 2,3-dichloro-5,6-dicyano-1,4-benzoquinone (DDQ) in refluxing benzene or silver (I) oxide in refluxing 1,4-dioxane afforded juglone (5-hydroxy-1,4-naphthoquinone) (1) in good yield. With manganese dioxide in dioxane the tetralone gave a mixture of juglone and naphthazarin (5,8-dihydroxy-1,4-naphthoquinone) (3), the proportion of naphthazarin being increased by the presence of water. Silver (I) oxide in 1,4-dioxane converted 9,10-dihydroxy-1-oxo (14),9,10-dihydroxy-1,5-dioxo (15), and 1,8-dioxo-1,2,3,4,5,6,7,8-octahydro anthracene (16) into, respectively, 1-hydroxy-5,6,7,8-tetrahydro (23), 1,5-dihydroxy (6), and 1,8-dihydroxy-9,10-anthraquinone (4), in high yield. Mechanisms for these transformations are discussed.